Supplements containing ephedrine - are they safe? Do they work? - Clarkson, P. M. (2001)
The few studies that examined ephedrine as an ergogenic aid have not found significant benefits, and serious adverse events have resulted from taking ephedrine prior to strenuous exercise. Ephedrine is banned by the International Olympic Committee (IOC) and the National Collegiate Athletic Association (NCAA) so that taking products containing ephedrine will result in a positive drug test and disqualify an athlete. Thus, it appears that the risks of ephedrine use outweigh any potential ergogenic benefits. Ephedrine ingestion can produce small losses in body weight. However, because weight loss is so small, products have been developed that combine ephedrine with caffeine and aspirin, which increase ephedrine's stimulatory effects. Although the combination is a more effective weight-loss agent, it also increases the likelihood of adverse events by enhancing stimulation of the central nervous system and the cardiovascular system. Those interested in using such products for weight loss should first consult with a physician.